Progress of Alkaline Anion Exchange Membranes for Fuel Cells: The Effects of Micro-Phase Separation - Xu, Fei; Su, Yue; Lin, Bencai (Frontiers in Materials, 2020)
Compared with that of proton exchange membrane fuel cells (PEMFCs), alkaline anion exchange membrane fuel cells (AEMFCs) with alkaline anion exchange membranes (AEMs) as electrolytes are attracting increased attention due to their potential use as non-precious catalysts. As one of the key components of AEMFCs, an ideal AEM must possess high hydroxide conductivity, good thermal stability, sufficient mechanical stability, and excellent long-term durability at elevated temperatures in an alkaline environment. Until now, a large number of AEMs with various chemical structures and properties have been prepared, and studied in detail, and it has been found that the microphase separation structure greatly affected the performance of AEMs. This minireview provides recent progress made of AEMs with hydrophilic/hydrophobic microphase separation structure. The hydroxide conductivity, alkaline stability, and mechanical properties of AEMs could be improved due to the formation of hydrophilic/hydrophobic microphase separation in the membranes. The relationship among the microphase separation, the chemical structure of the polymers, and the performance of membranes has been discussed in detail. This article attempts to give an overview of some key factors for the future design of novel AEMs with excellent performance such as high conductivity and improved chemical stability.